Polymer electrolytes based on Poly(VdF-co-HFP)/ionic liquid/carbonate membranes for high-performance lithium-ion batteries. (31st May 2019) - Tseng, Yu-Chao; Wu, You; Tsao, Chih-Hao; Teng, Hsisheng; Hou, Sheng-Shu; Jan, Jeng-Shiung
Abstract: In this study, we prepared the electrolytes by mixing the poly(vinylidene fluoride-co-hexafluoropropylene) (poly(VdF-co-HFP)) with 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM-TFSI), ethylene carbonate (EC) and lithium bis(trifluoromethanesulfonyl) imide (LiTFSI) in several weight ratios. The as-prepared electrolytes reveal micropores with various morphologies depending on the added EC content. They also exhibit glass transition temperatures lower than 0 °C, decomposition temperatures higher than 200 °C and good limited oxygen index to about 34 wt%. Moreover, the addition of EC facilitates the improvement of ion transport without compromising the electrochemical stability, consequently resulting in high ionic conductivity around 2.3 × 10 −3 S/cm at room temperature and a wide electrochemical window. In particular, the Li/LiFePO4 cells assembled with the electrolytes deliver remarkable discharge capacities of 143 mAh g −1, 120 mAh g −1 and 15 mAh g −1 at 0.2 C, 1 C and 5 C rates, respectively, with excellent capacity retention over 300 cycles at a rate of 0.2 C, as well as great interfacial stability after long-term cycling of charge-discharge. This study, in summary, provides a simple approach to prepare a quaternary electrolyte system and the findings indicate that the polymer electrolytes can be applied for high-performance LIBs. Graphical abstract: In this work, we prepared the electrolytes by mixing the poly(vinylidene fluoride-co-hexafluoropropylene) (poly(VdF-co-HFP)) with 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM-TFSI), ethylene carbonate (EC) and lithium bis(trifluoromethanesulfonyl) imide (LiTFSI). It was found that the electrolytes reveal different sizes of micropores depending on the EC content. The proper addition of EC would construct the surface morphology with regular distribution of micropores, which is conducive to the battery performance.Image 1 Highlights: A series of polymer electrolytes with high thermal stability were prepared. The electrolyte has high ionic conductivity around 2.3 × 10 −3 S/cm at room temperature and a wide electrochemical windows. The electrolytes deliver remarkable discharge capacities of 143 mAh g -1, 120 mAh g -1 and 15 mAh g -1 at 0.2 C, 1 C and 5 C rates, respectively, with excellent capacity retention over 300 cycles at a rate of 0.2 C.